Sport nutrition and doping in tennis: An analysis of athletes` attitudes and knowledge - Kondric, M.; Sekulic, D.; Uljevic, O.; Gabrilo, G.; Zvan, M. (Journal of Sports Science & Medicine, 2013)
Nutrition and doping issues are rarely studied in the sport of tennis. The aims of this investigation were to determine knowledge on doping (KD) and knowledge on sport nutrition (KSN), and corresponding socio-demographic-, sport-, and sport-nutrition- and doping-factors among an international sample of high-level tennis players of both sexes (43 females; 22 years old on average). In the first phase of the investigation, the KSN and KD questionnaires were studied for their reliability and validity. The consumption of NS is found to be very high, with almost of all the females and 80% of the males using NS at least occasionally. The athletes showed a low tendency regarding future doping usage, although most of them are convinced that doping does exist in tennis. Since athletes declared that their coaches are their main source of information about NS and doping, future studies should investigate what coaches actually know about such problems. KSN has been found to be protective against potential doping behavior in the future. Males are found to be more prone to doping than females. Therefore, in order to prevent doping behavior in tennis we strongly suggest intensive educational programs on sports nutrition and doping-related problems.